Walt Disney : the triumph of the American imagination - Gabler, Neal.; Leoncavallo, Leonardo (New York : Random House, Inc, 2006)
A portrait of the private life and public career of Walt Disney ranges from his deprived youth, to his contributions to the art of animation, to his visionary creation of the first synergistic entertainment empire, to his reclusive and lonely private world
Read by Leonardo Leoncavallo.
Keywords: Disney, Walt, -- 1901-1966.; Animators -- United States -- Biography